Effectiveness of community mental health nurses in an integrated primary care service: An observational cohort study - Mark Kenwright; Paula Fairclough; Jason McDonald; Louisa Pickford (Elsevier, 2024)
Background: The movement of community mental health nurses into primary care is important for the delivery of primary care integrated teams. There is little evidence or guidance on how integration should be implemented, or on the effectiveness of mental health nurses in primary care. Objectives: 1. Examine one method of integrating community mental health nurses in a primary care mental health service to identify factors that both facilitated and hindered integration. 2. Report on the outcomes of community mental health nurses in delivering problem-specific evidence-based psychological interventions in primary care. Design: A naturalistic observational cohort study Setting: An integrated primary care mental health service in the UK North Midlands Participants: 1,582 referrals from 1st April 2019 - 31st March 2022. Method: Anonymised patient records from routine treatment with community mental health nurses in an integrated primary care service were extracted and analysed to identify patient characteristics, content of treatment and outcomes. Features of service design were also examined to report on aids and barriers to primary care integration. Results: Large and clinically significant pre to post treatment effect sizes of between 0.5 and 0.8 were observed in symptom reduction and functional improvement for patients treated by community mental health nurses for a range of mental health problems. Aids to integration were: A single line of clinical management and governance; shared training across all roles; a shared IT system/electronic appointment diary. Barriers to integration were: Different contract management structures, and different clinical IT systems across primary and secondary care. Conclusions: Integrating community mental health nurses into one primary care mental health service comprising different mental health professionals provided a single point of access to different mental health treatments. Primary care community mental health nurses delivered effective evidence-based psychological interventions in a stepped-care model that reduced demands on secondary care services.